ChemInform Abstract: Diastereoselective Synthesis of 5‐Iminooxazolines and Their Subsequent Transformation to α, α‐Disubstituted Dipeptide Esters: A Formal [4 + 1] Cycloaddition Reaction of Cyclohexyl Isocyanide and Z‐Alkyl‐α‐benzoyl Amino‐Acrylates. Issue 5 (13th February 2013) - Esmaeili, Abbas Ali; Shahmansouri, Shima; Habibi, Azizollah; Fakhari, Ali Reza
Abstract Reaction of Z‐α‐benzoyl amino‐acrylic acid alkyl esters (I) with cyclohexyl isocyanide (II) gives iminooxazolines (III) under solvent‐free conditions.